2019
DOI: 10.1029/2018jd028750
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Deuterium Excess Variations of Precipitation at Summit, Greenland, and their Climatological Significance

Abstract: The hydrogen and oxygen isotopic composition of ice cores from Summit, Greenland, has provided invaluable information about variations in past climate. However, interpretations of these isotopic data have been made despite a paucity of direct isotopic studies of Summit precipitation. We provide insight to such interpretations by examining the annual cycle of deuterium excess (d‐excess) in precipitation samples from Summit and by considering the climatic controls on the annual cycle. Precipitation was collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
49
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 67 publications
(153 reference statements)
10
49
1
Order By: Relevance
“…Observations of water vapor isotopes at Summit (Greenland) carried out by Berkelhammer et al (2016) suggest that moisture sublimated from the ice sheet surface can recondense on fog particles, and ultimately returns to the ice surface under stable conditions associated with temperature inversion during summertime nights. More recently, high values of d-excess in summer precipitation and low values in winter precipitation at Summit (Greenland) were observed by Kopec et al (2019), a pattern opposite to that found at most high-latitude locations. They propose that the observed summer d-excess maximum at Summit is due to the contribution of high d-excess moisture from sublimation of surface snow on the Greenland Ice Sheet.…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 85%
“…Observations of water vapor isotopes at Summit (Greenland) carried out by Berkelhammer et al (2016) suggest that moisture sublimated from the ice sheet surface can recondense on fog particles, and ultimately returns to the ice surface under stable conditions associated with temperature inversion during summertime nights. More recently, high values of d-excess in summer precipitation and low values in winter precipitation at Summit (Greenland) were observed by Kopec et al (2019), a pattern opposite to that found at most high-latitude locations. They propose that the observed summer d-excess maximum at Summit is due to the contribution of high d-excess moisture from sublimation of surface snow on the Greenland Ice Sheet.…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 85%
“…Rayleigh distillation alters d-excess through a nonlinear evolution of the δD-δ 18 O trajectory as moisture in an air mass progressively condenses and rains out (Craig, 1961;Majoube, 1971;Ciais and Jouzel, 1994;Dutsch et al, 2017). Kopec et al (2019) demonstrated that Rayleigh distillation can help explain the relatively low d-excess values in winter Summit precipitation. On the other hand, Summit d-excess in the summer is extraordinarily high, which they explained via moisture contribution from sublimation of surface snow on the Greenland Ice Sheet along the air mass transport path.…”
mentioning
confidence: 99%
“…Despite the depth of information we have learned from these measurements in ice cores, a recent study has shown that there may be more to the story than we presently understand, particularly regarding the deuterium excess records. While Feng et al (2009) demonstrated that almost all sites in the mid-to high-latitudes of the Northern (and Southern) hemisphere exhibit an out-of-phase relationship between δD and d-excess, and the mechanisms controlling this pattern are relatively well understood, Kopec et al (2019) recently reported a nearly inphase relationship between δD and d-excess of event-based precipitation measurements at Summit, Greenland. This unique relationship requires additional investigation into the mechanisms controlling the water isotope record, primarily d-excess, at Summit.…”
mentioning
confidence: 99%
See 2 more Smart Citations